Islamic excellence achievement spirit: a strategy to drive knowledge sharing behaviour and adaptive selling capability - Ken Sudarti; Wasitowati Wasitowati (Jurnal Siasat Bisnis, 2021)
Knowledge sharing is still becoming a concern for many researchers because of the various positive impacts encountered. However, many individuals are still hesitant to do so, especially in a competitive environment where 'knowledge is power'. Knowledge sharing is often conducted only for the purpose of self-imaging and mutual benefits. Various studies that try to explore the antecedent variable of knowledge sharing behavior rarely use an Islamic motivational perspective. Hence, this article offers a new concept of Islamic excellence achievement spirit which is expected to be a cornerstone to improve knowledge sharing behavior. This new concept is the result of synthesis from the need for achievement theory, social capital theory, and Islamic values. The 291 sharia insurance employees in Indonesia were used as respondents of this study. Respondents obtained by using snowball sampling combined with purposive sampling. Regression analysis is used to test the empirical research model. The results show that Islamic excellence achievement spirit is proven to be able to increase knowledge sharing behavior that has an impact on increasing adaptive selling capability.